Infant Distress in a Food Delay Task Changes With Development and Predicts Amount Consumed - Stein, Sara F.; Riley, Hurley O.; Kaciroti, Niko; Rosenblum, Katherine L.; Sturza, Julie M.; Gearhardt, Ashley N.; Grogan-Kaylor, Andrew C.; Lumeng, Julie C.; Miller, Alison L. (Frontiers in Nutrition, 2022)
Objective: Eating behavior regulation emerges during early development and involves general self-regulation (emotional, behavioral), appetite regulation (homeostatic metabolic need) and appetite self-regulation (including both Bottom-Up Food Approach and Bottom-Up Food Avoidance and top-down purposeful self-control of eating). Limited research has investigated developmental trajectories of the regulation of eating behavior before the preschool years. The current study used a novel food delay task to assess infant distress as an early-emerging marker of eating behavior regulation constructs across early infancy and examine associations with amount of milk consumed. Method: Mother-infant dyads (n = 179) completed the Ability to Delay Gratification for Food in Infants Task (ATDG-FIT) at 2 weeks, 8 weeks, and 16 weeks of age. The ATDG-FIT required infants to wait before being fed while their bottle was present, but not accessible (3-minute Pre-Feeding Delay). After this, the infant was fed for 1 minute, then the feeding was paused for 30 seconds (Mid-Feeding Delay). Infant distress was coded during each feeding delay period and the amount of milk consumed was measured. Results: The mean proportion of distress during the Pre-Feeding Delay period decreased from 8 to 16 weeks of age (F(2,230) = 15.02, p < .001), whereas the mean proportion of distress during the Mid-Feeding Delay increased from 2 weeks to 8 weeks of age (F(2,230) = 27.04, p < .001). There was a positive interaction between distress during Mid-Feeding Delay and infant age predicting the amount consumed in the protocol (ß = .30, p = .022), suggesting that the association between distress during this part of the task and amount consumed strengthens as infants get older. Conclusions: The ATDG-FIT may be an effective method to assess emerging eating behavior regulation constructs during early infancy.